Philosophical ontology as a category theory: a logical approach (Actual Problems of Mind, 2017)
The paper gives account of some key conceptions of a philosophical ontology in the modern analytic philosophy. It is argued that such conceptions are usually understood as a category theory developed by means of a logical methodology.
Keywords: philosophical ontology; category theory; logical approach